ASSESSMENT OF DIGITAL MIGRATION SWITCH-OVER PREPAREDNESS AMONG SELECT BROADCAST STATIONS IN BENIN CITY - JOSEPHINE OSATOHANMWEN ADEYEYE; EMEKE PRECIOUS NWAOBOLI (International Studies Journal)
The researchers assessed the digital migration switch-over preparedness among select broadcast stations in Benin City. The rationale of the study was to ascertain the state of digital switch-over programme among broadcast stations in Benin City and how prepared select broadcast stations are in the switch over policy. Anchored on the Technological Determinism Theory, the researcher employed the survey research method and questionnaire as data collection instrument. The population of the study covers broadcasters from select broadcast stations in Benin City and the purposive sampling technique was used in administering 186 copies of questionnaire on the sample size that was arrived at using Roger Wimmer sample size determiner. Findings of the study revealed, among others, were that the level of preparedness and extent of adoption of DMSO was low and there are factors militating the full migration to digital broadcasting. The researchers recommended, among others, that broadcasting stations, especially smaller ones, would benefit from financial support or incentives provided by regulatory authorities or industry associations to aid in the acquisition of digital broadcasting equipment and infrastructure upgrades.